Dissociated disorders of speaking and writing in aphasia. Issue 6 (June 1978) - Basso, A; Taborelli, A; Vignolo, L A
Abstract : Of 500 left brain-damaged patients with educational level above elementary school investigated with a standard quantitative battery for dissociation between oral and written expression, speech was found to be selectively impaired in seven (three with "pure anarthria, " two with anarthria in the context of Broca's aphasia, and two with fluent aphasia with remarkable sparing of writing), and writing in another seven (two with "pure" agraphia, two with "agraphia with mild alexia, " and three with "agraphia with mild fluent aphasia.") The nature of three conditions (pure anarthria, fluent aphasia with sparing of writing, and pure agraphia) is discussed, with evidence of a selective association between pure agraphia and lesions of the upper left parietal lobule.